(untitled) (Journal of Parents and Teachers, 2026)
Analyses the duality between critical and creative thinking in education. He argues that teachers should devote less time to content and more to students working through debate, research and group work. To explain these skills, he uses the hypothesis of the cerebral hemispheres, which associates the right hemisphere with intuition and the left with rationality.